2018
DOI: 10.1590/1983-21252018v31n127rc
|View full text |Cite
|
Sign up to set email alerts
|

Population Density on Cowpea Cultivars With Different Growth Habits in the Matopiba Region

Abstract: The aim of this study was to assess the productive performance of cowpea cultivars with different growth habits as a function of population density in the MATOPIBA region, Brazil. The experiments were carried out in Magalhães de Almeida, MA in the agricultural season 2014/2015. The cultivars BRS Itaim, BRS Tumucumaque, and BRS Pajeú, which present an erect, semi-erect, and semi-prostrate growth habits, respectively, were assessed. For the erect and semi-erect cultivars, a total of 8, 12, 16, 20, 24, and 28 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
(7 reference statements)
1
7
0
2
Order By: Relevance
“…A similar result was observed by Cardoso, Melo and Ribeiro (2018), who evaluated the production performance of three cowpea cultivars of different types of growth habit, as a function of population density, in the MATOPIBA region, and observed that the production component most correlated with grain yield was the number of pods per area.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A similar result was observed by Cardoso, Melo and Ribeiro (2018), who evaluated the production performance of three cowpea cultivars of different types of growth habit, as a function of population density, in the MATOPIBA region, and observed that the production component most correlated with grain yield was the number of pods per area.…”
Section: Resultssupporting
confidence: 83%
“…Reduction of NPP with increased plant density was also observed by Cardoso, Melo and Ribeiro (2018), who evaluated the production performance of three cowpea cultivars with different types of growth habit as a function of population density, in the MATOPIBA region, and concluded that the number of pods per plant responded linearly to the increase in plant density, indicating that for the increase of one plant per square meter, there were reductions of 0.213, 0.166 and 0.378 pods per plant for cultivars with upright, semi-erect and semiprostrate growth habits, respectively.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…A produtividade máxima de grãos obtida para a cultivar Guariba está relacionado principalmente ao porte da planta que foi favorecida pelas condições climáticas da savana. Pesquisas relatam que genótipos de feijão-caupi de porte semi-eretos apresentam os maiores rendimentos, quando cultivados em grandes densidades populacionais (CARDOSO et al, 2018).…”
Section: Resultsunclassified
“…Since 2015, Midwest Region afforded the second major region producer in the rank of cowpea production, followed by Northeast [1], due to many efforts in achieving completely mechanized cropping, whereby cropping fields and grain yield has been enlarging mainly in Mato Grosso state [2]. Currently, the decreasing of cowpea productivity in Northeast region is due to inappropriate technological agricultural practices, such as low-density plant population in the field, sowing non-bred seeds, and mainly cropping in nitrogen deficient soils [3,4,5]. But, in North and Northeast regions the seeds used by farmers are mainly the grains the producers save from the previous year production, without regards to the vigor of the seeds that must be substituted by five and five years.…”
Section: Introductionmentioning
confidence: 99%